2019
DOI: 10.6023/cjoc201806021
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the Synthesis of Cinnoline Derivatives

Abstract: Cinnolines are "privileged scaffold" in new material and drug research, and development for their extensive biological activities such as anticancer, antibacterial, antiviral, anti-inflammatory, and sedative activities and good electron-accepting ability. As a result, the development of new synthetic routes to this important structure has been actively investigated in recent years. Especially, the C-H functionalization strategy has promoted the development of new methods greatly. The recent advances of the syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Simple 1H-benzo[de]cinnolines have been prepared by Lacy and Smith, Scheme 1(a) 5 and 1(b), 6 and by Aksenov, Aksenova et al, 7 Scheme 1(c). Using the methods represented in Scheme 1(a), a series of 1H-benzo[de]cinnolines have been prepared (Figure 2) by Mezheritskii et al, [8][9][10][11][12][13] A totally different method has been reported by Chenoweth et al, 8 (cited in 9 ). A very complex and beautiful reaction, starting from 3,6-dimethyl-1,2,4,5-tetrazine and o-benzyne, allows to prepare compound 20, 4-methyl-6-phenyl-6H-dibenzo[de,g]cinnolin 10 They have prepared a large set of compounds, 20-32, and some dimethyl derivatives starting from 4,5-dimethyl-o-benzyne (Scheme 2).…”
Section: Synthetic Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Simple 1H-benzo[de]cinnolines have been prepared by Lacy and Smith, Scheme 1(a) 5 and 1(b), 6 and by Aksenov, Aksenova et al, 7 Scheme 1(c). Using the methods represented in Scheme 1(a), a series of 1H-benzo[de]cinnolines have been prepared (Figure 2) by Mezheritskii et al, [8][9][10][11][12][13] A totally different method has been reported by Chenoweth et al, 8 (cited in 9 ). A very complex and beautiful reaction, starting from 3,6-dimethyl-1,2,4,5-tetrazine and o-benzyne, allows to prepare compound 20, 4-methyl-6-phenyl-6H-dibenzo[de,g]cinnolin 10 They have prepared a large set of compounds, 20-32, and some dimethyl derivatives starting from 4,5-dimethyl-o-benzyne (Scheme 2).…”
Section: Synthetic Methodologiesmentioning
confidence: 99%
“…These values will be compared with the calculated chemical shifts (Section 6). Like most recent papers, the experimental part contains 1 H NMR [9][10][11][12][13]30,31,[37][38][39]44 and 13 C NMR 11,37,43 data. 15 N NMR data are however still scarce 37 (see Section 7).…”
Section: Nmr Spectroscopymentioning
confidence: 99%